Malay traditional musical instruments as smartphone application / Ahmad Faiz Fazli Rosli - Rosli, Ahmad Faiz Fazli (2014)
People nowadays are keep forgetting their own local traditional musical instruments. Instead of learning or playing with the old school instruments, they prefer to the modern one such as electric guitar, bass, piano, drums and many more which are mostly come from outside. Smartphone is a device that most of the people in the world have. There are tons of attractive application in smartphone or can be download. Through this, new approach has been founded which is combining the old musical instruments with modern technology which is making it as smartphone application. There are big chance that people will download and learn to know more about Malay Traditional musical instruments. The apps will be made as attractive with others so that it can compete with apps that made by outsiders. Through this apps, the users can learn about the history and the background of the music instruments. Furthermore, they can hear the actual sound of those musical instruments by tapping on their smartphone screen. To know what people will think about this new application, a set questionnaire has been distributed to 50 UITM Malacca city campus students. Most of the question will ask about their opinion about, the new apps and they their answers will be collected and presented through analysis.